#import "@youwen/zen:0.1.0": * #show: zen.with( title: "Homework 5", author: "Youwen Wu", ) #set heading(numbering: none) #show heading.where(level: 2): it => [#it.body.] #show heading.where(level: 3): it => [#it.body.] #set par(first-line-indent: 0pt, spacing: 1em) Problems: 2.4: \#4bcde, 5ajq, 6ce, 7a, 9, 10, 12abc 2.5: \#1abc, 3, 10 #outline() = 2.4 == 4 === b $3 + 11 + 19 + dots.c + (8n - 5) = 4n^2 - n$ First we show the base case for $n = 1$. $ 3 = 4 (1^2) - 1 = 3 $ Now we proceed by induction. Assume $sum _(k=1) ^n (8k-5) = 4(n^2) - n$. $ sum_(k=1)^(n+1) (8k-5) &= 4((n+1)^2) - (n+1) \ (sum_(k=1)^(n) (8k-5)) + (8(n+1) - 5) &= 4(n^2 + 2n + 1) - n-1 \ (sum_(k=1)^(n) (8k-5)) + 8n + 3 &= 4n^2 - n + 8n + 3 \ (sum_(k=1)^(n) (8k-5)) &= 4n^2 - n \ $ and we know that this is true by our original assumption. So by the PMI, this is true $forall n in NN$. === c $sum_(i=1)^n 2^i = 2^(n+1) - 2$ For the base case: $ 2^1 = 2(1 + 1) - 2 \ 2 = 2 $ Assume that $ sum_(i=1)^n 2^i = 2^(n+1) - 2 $ Proceeding by induction, $ sum_(i=1)^(n+1) 2^i = 2^(n+1+1) - 2 \ (sum_(i=1)^(n) 2^i) + 2^(n+1) = 2^(n+2) - 2 \ (sum_(i=1)^(n) 2^i) = 2^(n+2) - 2^(n+1) - 2 \ (sum_(i=1)^(n) 2^i) = 2^(n+1) dot (2 - 1) - 2 \ (sum_(i=1)^(n) 2^i) = 2^(n+1) - 2 \ $ So by the PMI, it holds for all $n in NN$. === d $1 dot 1! + 2 dot 2! + 3 dot 3! + dots.c + n dot n! = (n + 1)! - 1$ For the base case: $1 dot 1! = (1 + 1)! - 1 \ 1 = 1$ Assuming the inductive hypothesis, $ sum^n_(k=1) k dot k! = (n + 1)! - 1 \ $ Now we proceed by induction $ sum^(n+1)_(k=1) k dot k! = (n + 2)! - 1 \ sum^(n)_(k=1) k dot k! + (n + 1) dot (n+1)! = (n + 2) dot (n + 1)! - 1 \ sum^(n)_(k=1) k dot k! = (n + 2) dot (n + 1)! - (n + 1) dot (n+1)! - 1 \ sum^(n)_(k=1) k dot k! = (n + 1)! dot (n+2 - (n + 1) - 1 \ sum^(n)_(k=1) k dot k! = (n + 1)! - 1 \ $ So by the PMI, this is true for all $n in NN$